VKORC1-based resistance to anticoagulant rodenticides widespread in Finnish house mice but not in brown rats - Aivelo, Tuomas; Koivisto, Elina; Esther, Alexandra; Koivisto, Sanna; Huitu, Otso (Informa UK Limited, 2023)
Anticoagulant rodenticide (AR) resistance is widespread across Europe, but its prevalence has not been previously studied in Finland. We sampled 48 house mice (Mus musculus) and 48 brown rat (Rattus norvegicus) in farms and urban locations from southern Finland and here we report the identification of Vkorc1 polymorphisms linked to AR resistance. Two thirds of mice carried Vkorc1 polymorphisms. The most common was the type Y139C (resistance to first-generation ARs, bromadiolone and difenacoum), whereas the type L128S (resistance to FGARs and bromadiolone) was much less abundant. Only two rats tested positive, both with a rare type R33P (resistance probably to warfarin). No clear patterns based on subregion, sex and urban/rural division were seen. We suggest that the type Y139C polymorphism should be taken into account when planning control actions targeting house mice in Finland. The low number of AR resistant rats found suggests a low prevalence of resistance in rats. To fully understand the state of AR resistance in Finland, additional studies on yellow-necked mouse (Apodemus flavicollis) and bank voles (Myodes glareolus) are needed.